Synthesis and Characterization of Some Four-Coordinated Pt(II) Coordination Compounds of Semicarbazones Derived from 4-Aminoantipyrine - Singh, Lakshman; Gupta, Pravin; Upma Singh, Ms.; Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
In the present work, we describe a novel series of eleven platinum(II) coordination compounds of semicarbazones derived from 4-aminoantipyrine and various aryl aldehydes with the general composition Pt(L)Cl2. All these coordination compounds have been characterized through various physico-chemical studies. The infrared and electronic spectral studies suggest that the ligands act as tridentate (N, N, O) donors and the diamagnetic coordination compounds have square-planar geometries.